2017
DOI: 10.21125/inted.2017.1109
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, Cyberbullying and Social Support: A Study in a Portuguese School

Abstract: This paper presents a study that was developed with a sample of middle and high school students of the 3rd cycle of a Portuguese school, with an average age of 13.52 years (SD = 0,96) and an almost equal distribution in terms of sex (73 males vs. 70 females) and schooling (44 in the 7th year, 49 in the 8th year and 50 in the 9th year). The results show a prevalence of Observation Behaviour in the Victimization Scale and School Aggression and the dimension Satisfaction with Family in Satisfaction Scale Social S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…One of these internal factors is life satisfaction. Several previous studies showed a negative relationship between life satisfaction and cyberbullying [29]; [30]; [31]; [32]; [33]. The results of these studies explain that the low life satisfaction affects the tendency to do cyberbullying.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…One of these internal factors is life satisfaction. Several previous studies showed a negative relationship between life satisfaction and cyberbullying [29]; [30]; [31]; [32]; [33]. The results of these studies explain that the low life satisfaction affects the tendency to do cyberbullying.…”
Section: Introductionmentioning
confidence: 56%
“…The aspects of life satisfaction that do not significantly affect cyberbullying are family satisfaction. Arriaga et al [32] found that high satisfaction with the family is related to the high level of cyberbullying. This can be because all samples are active social media users with a duration of more than an hour per day.…”
Section: Discussion and Suggestionmentioning
confidence: 99%
“…been found to influence emotional responses to CB. Other factors associated with emotional responses and coping strategies include family factors such as parents' education, parents' careers (20)(21)(22), family income (23)(24)(25)(26), social support from family and friends (27)(28)(29)(30)(31)(32)(33)(34), and social stress (33,35).…”
Section: Introductionmentioning
confidence: 99%